2011
DOI: 10.1188/11.cjon.23-25
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Evidence-Based Inpatient Medical Oncology Fluid Balance Measurement Policy

Abstract: Fluid balance measurement (FBM) is a routine intervention in oncology, but accuracy and compliance issues have been documented. This article describes how a medical oncology nursing clinical practice committee used the Iowa Model for Evidence-Based Practice to establish a policy for FBM. Nursing and medical education was performed with emphasis on oncology-specific defaults in a computerized provider order entry system reflecting the new FBM policy. At two months of implementation, the policy effectively demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In total, we excluded 15 studies after full copies of papers were obtained and scrutinised (Alexander 2011; Anonymous 2009; Artz 2011; Callaghan 1998; Gracias 2008; Hampton 2005; Johnson 2011; Kavanagh 2006; Lee 2009; Lenz 2009; Levin 2011; McKinley 2007; Scheide 2007; White 2010; Whitney 2006). The reasons for exclusion are presented in the Characteristics of excluded studies table.…”
Section: Resultsmentioning
confidence: 99%
“…In total, we excluded 15 studies after full copies of papers were obtained and scrutinised (Alexander 2011; Anonymous 2009; Artz 2011; Callaghan 1998; Gracias 2008; Hampton 2005; Johnson 2011; Kavanagh 2006; Lee 2009; Lenz 2009; Levin 2011; McKinley 2007; Scheide 2007; White 2010; Whitney 2006). The reasons for exclusion are presented in the Characteristics of excluded studies table.…”
Section: Resultsmentioning
confidence: 99%
“…The studies comprised 12 studies categorised as quasi-experimental,33 40–43 45–47 49–51 54 3 cohort studies32 37 44 and 8 prevalence studies (cross-sectional studies) 34–36 38 39 48 52 53. All were appraised using the JBI tools for assessing quasi-experimental and prevalence studies.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in weight in the short period are largely due to changes in the body's total water. Knowledge of the intensity and direction of this parameter may exert great relevance in the diagnosis and treatment of complex disorders of the electrolyte balance (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Nursing care is responsible for ensuring that water balance printouts are accurately and accurately recorded. (22) Descriptive, exploratory/ VI* The nursing team identified that entry and exit measures are useful and necessary for at-risk populations. The Iowa Model for Evidence-Based Practice guided the change in practice.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation